Project management challenges and difficulties: A case study of information system development - Lucky, Esuh Ossai-Igwe; Adegoke, Ojeniyi; Othman, Noraini (Othman Yeop Abdullah (OYA) Graduate School of Business, Universiti Utara Malaysia, 2014)
The successful development of Information System (IS) is not high even with enormous interest and fund committed by organizations on this new technology.It has been revealed that a combination of insufficient and unsuitable project management issues are responsible for this low rate of IS development.This paper presents the findings of the fieldwork and interview conducted on the challenges and difficulties of system development project.The study employed both personal interview and observation methods. The findings revealed that fund, infrastructures (hardware and software), manpower, management commitment, monitoring and inspection were the critical challenges and difficulties faced by organizations during their system development. Therefore, the study concludes that fund, infrastructures (hardware and software), manpower, management commitment, monitoring and inspection play crucial role for an effective system development.Our study recommends that there should be sufficient budget to procure the right system hardware and software for right requirements.Secondly, training of staff for both IS development and management should be given urgent attention.